Utilization of Rice Field Conch Shells as a partial substitution of Cement and Fine Aggregate for Split Tensile Strength of Concrete - Permatasari Nina; Bunyamin Bunyamin; Hady Munirul; Abu Hafiz Dhamar; Lathifah Nur; Auliyah Manna Husnul (E3S Web of Conferences, 2024)
Aceh is one of the provinces in Indonesia which has a very large area of rice field production. However, there are many pests that hinder agriculture in Indonesia. One of them is the rice field conch shells which has the potential to cause very high losses to the rice crop harvest. The aim of this research was to determine the ratio of the split tensile strength of concrete using rice field conch shells as a partial replacement for cement and fine sand against normal concrete by 0%, 5%, 10%, and 15%. In addition, it was also seen the effect of immersing concrete specimens using rice field conch shells substitution in tap water and water collected from paddy's farm. This study used the ACI (American Concrete Institute) 211.1-91 and ASTM (American Society for Testing and Materials) methods. The specimens consisted of cylinders with dimensions of 15 cm x 30 cm, totaling 40 specimens with a design concrete compressive strength of 17.00 MPa. The curing of the specimens was carried out using tap water and water collected from paddy's farm for 28 days in the soaking tub. The results showed that 5% substitution of rice field conch shells in cement and fine sand using the tap water immersion method showed a 3% increase in the tensile strength of concrete in comparison with normal concrete. Meanwhile, immersion using the water collected from paddy’s farm method showed a decrease in the value of the split tensile strength of the concrete.